2019
DOI: 10.1002/eat.23178
|View full text |Cite
|
Sign up to set email alerts
|

Negative psychological correlates of the pursuit of muscularity among women

Abstract: Objective There is increasing public and scientific focus on women's pursuit of a muscular and toned appearance. However, the psychological correlates of women's drive for muscularity are currently unclear. Therefore, we examined the associations of drive for muscularity with four important negative psychological indices among women: eating disorder (ED) symptoms, and symptoms of depression, anxiety, and stress. Method A sample of 221 university women completed an online survey that included measures assessing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 23 publications
1
18
0
1
Order By: Relevance
“…However, although the data suggest that muscularity was most prominent in college men, it is notable that muscle building was relevant for community and college women. This finding supports recent work highlighting the increasing prominence of muscle building and idealization of a muscular or toned ideal among women (Cunningham et al, 2019; Lipson et al, 2020).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…However, although the data suggest that muscularity was most prominent in college men, it is notable that muscle building was relevant for community and college women. This finding supports recent work highlighting the increasing prominence of muscle building and idealization of a muscular or toned ideal among women (Cunningham et al, 2019; Lipson et al, 2020).…”
Section: Discussionsupporting
confidence: 90%
“…On the other hand, those hoping to achieve a more muscular ideal may aim to increase caloric intake and engage in muscle‐building exercise to put on muscle mass. Most research on a preference for this muscular ideal has focused on men (Forrest, Perkins, Lavender, & Smith, 2019; Lavender, Brown, & Murray, 2017; Nagata, Ganson, & Murray, 2020), though recent work highlights the increasing prevalence of women who aim to achieve a muscular or toned physique and thus engage in muscle building behaviors to do so (Cunningham et al, 2019; Lipson, Stewart, & Griffiths, 2020). Despite evidence that exercise behaviors may differ based on gender and body image ideals, less is known about how these behaviors fit in with broader features associated with exercise pathology, such as compulsivity and emotion dysregulation.…”
Section: Introductionmentioning
confidence: 99%
“…Given that other work among male youth has identified relationships between muscularity‐oriented teasing and body image outcomes (e.g., Galioto et al, 2012), utilizing measures of teasing that can capture both of these aspects would be useful in future research. In addition, although the measures of body satisfaction included items assessing body areas that are of concern for males (such as shoulders), future research would benefit from utilizing measures that explicitly assess dissatisfaction related to muscularity as these are increasing concerns in youth across genders (Cunningham et al, 2019; Rodgers et al, 2018). Similarly, outcome measures that include muscularity‐targeted eating and exercise behaviors would also contribute to better capturing these relationships among male youth (Bentley, Gratwick‐Sarll, Harrison, & Mond, 2015; Murray et al, 2019; Trompeter et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Adolescent disordered eating and obesity traditionally have been linked to negative body image [1][2][3]. Studies of adolescent samples have demonstrated that the negative facets of body image, such as body dissatisfaction, drive for thinness or muscularity, overweight preoccupation, body shame and self-objectification are associated with poorer psychological and physical health, disordered eating and overweight development in future life [4][5][6][7][8][9][10]. Intensive efforts have been produced to create various body image concerns and disordered eating prevention programs for adolescents [11,12].…”
Section: Introductionmentioning
confidence: 99%